The left and the democratic stability in Latin America: the ideology of the Bolivarian Revolution and its impact on the political processes in Venezuela and Latin America - José Enrique MOLINA V. (América Latina Hoy, 2010)
One of the main areas of work in Comparative Politics and Political Theory has been the determination of the variables associated with the stability/instability of political systems in general, and democracy in particular. This paper focuses on one of these variables. One with newly acquired importance after the recent electoral successes by the left, but that nevertheless has not been in the spotlight of scholarly analysis: ideological polarization. Particularly, ideological polarization brought about by the attempt to pursue by the government a leftist political project. The main focus is on the ideological project pursued by the Venezuelan Bolivarian Government and its association with the political instability of 2002 and 2003. The paper considers this topic taken into account mainstream theoretical approaches on political stability, and the experience of previous Latin American leftist governments. The paper reaches the conclusion that in Latin America the attempt to implement a socialist program by a democratically elected government, if it is done without meaningful social and political negotiation, and with authoritarian overtones, is likely to lead to intense political instability and to the ultimate failure of the proposed social change.